ACTUALITY OF A COMPETENT PHILOLOGIST’S FORMING IN THE HIGHER EDUCATION SYSTEM OF SWITZERLAND - Заслужена, А. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
This article deals with the problem of forming competent philologist in higher educational institutions of Switzerland. The principles of this training have been analysed. Attention is paid to the development of competences students- philologists